Flow chart as a tool for improvement and control in public instuons - Carvalho, Alexandre Brondani; Abreu, Ivonisa Maria Castagna de; Pedrozo, Ivonete Foletto (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346593790 Controls are fundamental tools for the quality of the services provided by public and private organizations. The Supervising Permits Management of the City Hall of Santa Maria displays troubles regarding these controls. Thus, this study aims at describing the emission process of notifications sent by the Administration and also to suggest points of control, allowing Public Management to improve its collection, as well as avoiding the customers to be improperly charged. The present work was accomplished by a case study. Starting from a no structured interview, a flowchart has been developed, emphasizing the critical aspects to be improved. Standard operational procedures were proposed for those critical aspects in order to establish a routine, improving the performed processes. Besides, improving suggestions have been presented with the intent of optimizing the services for a higher satisfaction of the internal and external customer of the organization.